2022
DOI: 10.1038/s41598-022-19274-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal microarray analyses from 5778 patients with neurodevelopmental disorders and congenital anomalies in Brazil

Abstract: Chromosomal microarray analysis (CMA) has been recommended and practiced routinely since 2010 both in the USA and Europe as the first-tier cytogenetic test for patients with unexplained neurodevelopmental delay/intellectual disability, autism spectrum disorders, and/or multiple congenital anomalies. However, in Brazil, the use of CMA is still limited, due to its high cost and complexity in integrating the results from both the private and public health systems. Although Brazil has one of the world’s largest si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
2
6
0
1
Order By: Relevance
“…This has an implication of failing to detect uniparental disomy (UPD) and parental consanguinity or ploidy changes. Although detecting consanguinity has a debatable diagnostic value, UPD and ploidy changes are relevant but not frequent (i.e., UPD and consanguinity frequency in postnatal 26/5778 (Krepischi et al., 2022)). It is estimated that triploidy affects 1% of all conceptions but most of the affected fetus cannot survive the first trimester period and the majority of these pregnancies result in miscarriage (Eftekhariyazdi et al., 2019; Massalska et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has an implication of failing to detect uniparental disomy (UPD) and parental consanguinity or ploidy changes. Although detecting consanguinity has a debatable diagnostic value, UPD and ploidy changes are relevant but not frequent (i.e., UPD and consanguinity frequency in postnatal 26/5778 (Krepischi et al., 2022)). It is estimated that triploidy affects 1% of all conceptions but most of the affected fetus cannot survive the first trimester period and the majority of these pregnancies result in miscarriage (Eftekhariyazdi et al., 2019; Massalska et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Log 2 ratio and B Allele Frequency (in the case of SNP-arrays) values were plotted along genomic coordinates, and the chromosome regions with either copy number or allele frequency alterations were identified. SNP-array and array-CGH analysis were conducted according to parameters previously reported (Krepischi et al, 2022;Villela et al, 2017Villela et al, , 2021.…”
Section: Chromosomal Microarrays Analysis (Cma)mentioning
confidence: 99%
“…The scientific literature was retrieved from PubMed. After this analysis, the CNVs were classified as benign, likely benign, variants of uncertain clinical significance, likely pathogenic, or pathogenic, following the joint consensus recommendation of the American College of Medical Genetics and Genomics (ACMG) and the Clinical Genome Resource (ClinGen) [29, 30].…”
Section: Methodsmentioning
confidence: 99%
“…A Brazilian study revealed that in 5778 individuals with general neurodevelopmental disorder and/or congenital abnormalities without evident cause, CNVs were found in 1886 individuals classified as pathogenic, likely pathogenic, and VUS (41%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%